The Historical Center of Bellavista as a Monumental Area: Urban - Architectural analysis - Malpartida Pacaya, Patricia (2020)
The Historic Center of Bellavista, designed by Luis Godín in 1746, is in a process of degradation that has been occurring for several decades due to various factors such as abandonment, deterioration, change of land uses, demolitions, among others. The urban layout of the historic Bellavista, which encloses colonial and republican architecture within it, with the passage of time begins to disappear distorting the urban image that has great historical value for both the history of Callao and the history of Lima. Unfortunately there is little that has been investigated of the ancient buildings in this district, therefore, the present article reveals the urban and architectural studies that will identify the values of the Historic Center of Bellavista in order to achieve a possible declaration of monuments putting in value the historical zone of the district and stopping, as far as possible, this process of degradation that is going through. The present investigation is dedicated to the district that saw me grow up, Bellavista, my home.